The teaching of subjects related to pharmacovigilance in Malaysian pharmacy undergraduate programs - Elkalmi, Ramadan Mohamed Mahmod; Ahmad Hassali, MA; Al-lela, Omer Qutaiba; Jamshed, Shazia Qasim (OMICS Group, 2013)
Objectives: To evaluate the extent to which subjects related to pharmacovigilance are taught in the pharmacy programs within Malaysian universities. Methods: Self-completed questionnaires were sent (via surface mail) to all heads of schools and faculties of pharmacy and medicine that offer pharmacy programs in Malaysia. The questionnaires were intended for department heads or the person responsible for the teaching of the subject in the respective institutions. Results: Thirteen out of fourteen (n=13, 92.8%) medical and pharmacy schools responded to the survey. The vast majority (n=11, N=13, 84.6%) of the pharmacy programs within the studied Malaysian universities feature pharmacovigilance-related topics in their undergraduate syllabi. About two-thirds (n=8, 72.7%) of the pharmacy programs taught issues related to pharmacovigilance within epidemiology and/or pharmacoepidemiology courses. Pharmacovigilance-related topics are core/required in almost all (n=9, 81.8%) of the pharmacy programs. None of the pharmacy programs had a specific stand-alone course on pharmacovigilance. Conclusion: Subjects related to pharmacovigilance were widely taught in the majority of the universities surveyed. As the field of pharmacovigilance is very important for future pharmacy practitioners, this course should be made a core course within the local pharmacy curriculum in order to enhance medication safety for the population. To ensure effective practice in the area of drug safety, there is an urgent and necessary need for Malaysian pharmacy students to be adequately educated and exposed to the contemporary issues and challenges of pharmacovigilance implementation.